Characterization and analysis of the thermal damages of aramid/epoxy composite laminates induced by the dielectric heating effect of microwaves. (15th September 2018) - Xu, Xiangyu; Zhang, Boming; Xing, Liying; Liu, Kai; Bai, Ming; Liu, Dawei
Abstract: Aramid/epoxy composite is one of the most promising materials for fabricating wave-transmitting structural components due to its excellent dielectric and mechanical properties. The temperature field of a composite can be greatly influenced by the dielectric heating effect when exposed to electromagnetic environments. In this investigation, the composites were subjected to microwave radiation of different power densities. The equilibrium temperature, power thresholds and damage morphologies of quasi-isotropic laminates were compared with that of unidirectional composites. Following this, the mechanism of different responses to microwave radiations were analyzed. The obtained results indicate that for the same thickness the quasi-isotropic laminates have better resistance to microwave radiation as compared to unidirectional composites. Besides, the unidirectional composites tend to form oval-shaped damaged regions while the quasi-isotropic laminates form almost circular regions. Furthermore, at about 200 °C, the composites had a sudden increase in temperature that lead to thermal damage.